KEPEMIMPINAN TRANSFORMASIONAL DALAM PENGUATAN MANAJEMEN KELEMBAGAAN SEKOLAH PENGGERAK: STUDI PADA SMA NEGERI 5 PINRANG - muhammad alwi (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2025)
Abstract: This study aims to analyze the role of transformational leadership of the school principal in strengthening institutional management within the Sekolah Penggerak program at SMA Negeri 5 Pinrang. Employing a qualitative approach with a case study design, data were collected through in-depth interviews with the principal and the vice principal for curriculum affairs, and analyzed thematically. The findings reveal that transformational leadership is reflected in moral exemplarity, inspirational motivation, teacher empowerment, and the cultivation of sustainable institutional values. Leadership strategies are directed toward fostering collaboration, strengthening governance, and developing a reflective culture that adapts to the Merdeka Curriculum policy. The impact is evident in the increased teacher motivation, the shift toward a collaborative learning culture, and the reinforcement of school managerial systems. This study emphasizes transformational leadership as both a moral and institutional force, offering a value-based model for strengthening school institutions amid the ongoing transformation of Indonesia’s educational landscape. Keywords: Transformational Leadership, Independent Curriculum, Institutional Management, Driving Schools. Abstrak: Penelitian ini bertujuan menganalisis peran kepemimpinan transformasional kepala sekolah dalam memperkuat manajemen kelembagaan pada program Sekolah Penggerak di SMA Negeri 5 Pinrang. Menggunakan pendekatan kualitatif dengan desain studi kasus, data dikumpulkan melalui wawancara mendalam dengan kepala sekolah dan wakil kepala sekolah bidang kurikulum, kemudian dianalisis secara tematik. Hasil penelitian menunjukkan bahwa kepemimpinan transformasional tercermin dalam keteladanan moral, motivasi inspiratif, pemberdayaan guru, dan penanaman nilai kelembagaan yang berkelanjutan. Strategi kepemimpinan diarahkan untuk membangun kolaborasi, memperkuat tata kelola, dan menumbuhkan budaya reflektif yang adaptif terhadap kebijakan Kurikulum Merdeka. Dampaknya terlihat pada meningkatnya motivasi guru, perubahan budaya organisasi menuju pembelajaran kolaboratif, serta penguatan sistem manajerial sekolah. Penelitian ini menegaskan kepemimpinan transformasional sebagai kekuatan moral dan institusional yang relevan bagi penguatan kelembagaan sekolah di era transformasi pendidikan nasional. Kata kunci: Kepemimpinan Transformasional, Kurikulum Merdeka, Manajemen Kelembagaan, Sekolah Penggerak.